0059 A global perspective on coal-fired power plants and lung cancer mortality. (21st August 2017) - Lin, ChengKuan; Christiani, David; Lin, Ro-Ting
Abstract : Background: Lung cancer is the leading cause of cancer mortality in many countries and leads to substantial financial burden globally. The lack of consideration of the widely diverse compositions of particulate matter (PM) may lead to inaccurate estimation and inability to capture respective contributions as current estimates. Methods: Age- and sex-adjusted lung cancer mortalities of 61 countries were followed from 1979 to 2013 while 10-year-accumulative coal capacities is the primary independent variable. We applied a change-in-change model to estimate the preventable deaths of lung cancer from the changes of coal capacities during periods from 1999–2003 to 2009–2013, adjusting for various socioeconomic, demographic determinants, and lag period. Results: The average log coal capacity increased from 9·58 in 1980 to 10·35 in 2010, and smoking prevalence dropped by 13·82% among males in the same period. One log coal capacity (unit: logMW) was associated with an increase in lung cancer mortality by 58·31 per million males (SD=28·49, p<0·05); while the savings from decreasing smoking prevalence was only 4·86 per million males (SD=0·03, p<0·05). Based on the model, we estimated a total of 123·68 thousand lives could be saved from lung cancer among 3477 million males in 2011. Conclusion: This study answered a key policy question on the externality cost of coal power plants and estimated global disease burden from preventable lung cancer attributable to coal-fired power plants. By changing a nationwide energy matrix from brown energy to green, some European countries have prevented lung cancer mortality among males successfully.